ISOLATION AND PURIFICATION OF LIPASE FROM COCOA BEANS (Theobroma cacao. L.) OF CLONE PBC 159 - Ratna Agung Samsumaharto (Indonesian Journal of Chemistry, 2008)
Lipase (triacylglycerol acylhydrolase, EC 3.1.1.3) was extracted and purified from acetone dry powder of cocoa (Theobroma cacao. L.) of clone PBC 159 extract. The Lipase  from AcDP of cocoa beans was used for purification using 40-60 and 60-80% ammonium sulphate precipitation. The resulted indicated 44.73 and 60.51-fold purification with 26.74 and 33.31% recovery lipase activity (yield), respectively. The crude lipase enzyme from both precipitation were eluted, producing a single peak after applying through Sephacryl S-200 chromatography. The purified enzyme had a uniform specific activity throughout the final chromatography peak. The results from SDS-PAGE analysis showed that the molecular weight of the lipase enzyme was in between 45-66 kDa.